North American spoken English [videorecording] - Zerna, Gene. (Seoul Hong-Ik Media, 1993)
A practical, intensive speech, training in relaxed settings, for anyone who wants more command of spoken English. Includes speech exercises and drills, lip and tongue articulation and points of vibration, etc.
Tape 1. Tonal action (31 min.) -- Tape 2. Structural action (46 min.) -- Tape 3. Neutral vowels (30 min.) -- Tape 4. Consonant action (41 min.) -- Tape 5. More consonant action (46 min.) -- Tape 6. Connected speech (39 min.) -- Tape 7. Intonation/Rhythm patterns (44 min.) -- Tape 8. Practical scenes (40 min.) -- Tape 9. More practical scenes (70 min.)
Title on cover: Master spoken English.
VHS.
Credits : Susan Hayes, editor ; Connie Howard, dialectician ; Randy Talai, phonics specialist ; Gene Zerna, voice and speech specialist.
Keywords: English language -- Phonetics; English language -- Spoken English -- Study and teaching